ECOLOGICAL CHARACTERISTICS OF Castanopsis tungurrut (BLUME) A. DC ALONG THE ALTITUDINAL GRADIENT IN CIBODAS BIOSPHERE RESERVE - Nurdiana, Dian Ridwan; E. Buot, Jr, Inocencio (SEAMEO BIOTROP, 2025)
HIGHLIGHTS- Castanopsis tungurrut prefer mid-altitude forest habitat- The population show clumped pattern on steep slopes- Vegetation cluster shift with altitudinal gradient- Cisarua is the highest density of Castanopsis tungurrut ABSTRACTCastanopsis tungurrut is an endangered species that has received limited attention in terms of research, with scarce ecological information and description of its native distribution area, the Cibodas Biosphere Reserve. This study aimed to investigate the ecological characteristics, vegetation clusters, population structure, and habitat preferences of C. tungurrut along the altitudinal gradient. To assess the vegetation, a total of 41 plots were used, with dimensions of 20 × 20 m for trees, 10 × 10 m for poles, 5 × 5 m for saplings, and 2 × 2 m for wildings. The results revealed that the vegetation in four different locations (Cibodas, Bodogol, Cisarua, and Selabintana) within the altitude range of ca. 750 - 1800 meters above sea level (m asl) could be grouped into three distinct zone clusters based on the dominant species. These clusters were named Zone I (ca. 500 - 1,000 m asl), Castanopsis-Lithocarpus and Schima wallichii forest characterized by the dominance of Castanopsis tungurrut, Maesopsis eminii, and Schima wallichii; Zone II (ca. 1,000 -1,500 m asl), Castanopsis and Schima wallichii forest, dominated by Castanopsis (Fagaceae forest) and Schima wallichii; and Zone III (ca.1,500-2,400 m asl), Schima wallichii, Castanopsis, and Altingia excelsa forest where Schima wallichii, Castanopsis, and Altingia excelsa were prevalent. C. tungurrut was found to dominate at elevations between ca. 750 and 1,500 m asl, gradually decreasing in higher elevations or even absent. It exhibited a clumped distribution pattern, favoring steep to highly steep habitats. The highest population density was observed in Cisarua (53.1 individuals/ha), followed by Bodogol (25 individuals/ha), Cibodas (10.7 individuals/ha), and Selabintana (5 individuals/ha). These findings emphasize the species' selective habitat preferences, particularly with regard to altitude and slope factors, which should be taken into consideration when planning conservation efforts.